Determinan Kejadian Berat Badan Lahir Rendah pada Ibu Melahirkan Selama Pandemi Covid-19: Determinants for Low Birth Weight in Mothers Giving Birth during the Covid-19 Pandemic - Kurniasari, Lia; Kertasurya, Martha Irene; Nugraheni, Sri Achadi; Agushybana, Farid (Amerta Nutrition, 2024)
Background: Low birth weight (LBW) remains a significant global health issue, leading to higher rates of infant and child morbidity and mortality. In 2022, Indonesia had a 12.58% rate, while in Kutai Kartanegara Regency, East Kalimantan, the rate was higher at 16.30%. The Covid-19 pandemic, which severely impacted East Kalimantan also influenced LBW rates. Objectives: Analyzed the determinants of LBW incidence during the Covid-19 pandemic in Kutai Kartanegara. Methods: This population of 1265 mothers delivered in four public health centers with the highest cases of BBLR. This study used a case control design for 240 mothers, including 120 mothers who gave birth to babies with low birth weight and 120 mothers who gave birth to babies with LBW. Data were obtained from e-cohort data according to specific inclusion and exclusion criteria. Data collection occurred from August until October 2022 through interviews with structured questionnaires and maternal child handbooks. Data analysis was performed with logistic regression. Results: Determinant factors LBW were maternal nutritional risk (upper arm circumference <23.5 cm) (OR=2.800, 95% CI=1.237-6.340), history of anemia (OR=3.156, 95% CI=1.716-5.804), history of Covid-19 (OR=4.357, 95% CI=2.355-8.063), living with a smoker (OR=2.505, 95% CI=1.716-2.804), and not having health insurance (OR=2.744, 95% CI=1.435-5.247). Conclusions: Internal factors such as age, under arm circumference, anemia, Covid-19, birth spacing, and parity and external factors (such as living with smokers, not having insurance) were interconnected in contributing to the risk of LBW, the pandemic further influenced these determinant factors.